Visions of the 21st century family transforming structures and identities - Claster, Patricia Neff; Blair, Sampson Lee (Emerald, 2013)
One undeniable fact about families is that they keep changing, both in terms of structure and behavior. Many factors have served to bring about such changes, including social, cultural, political, and institutional change, resulting in family forms which perhaps may represent the new traditional in the not-so-distant future. Through research studies from around the world, this volume examines these changing structures and behaviors, and attempts to better illustrate the ever-changing nature of families. Topics covered include: transracial adoption, lesbian parenting, intergenerational relationships, procreative identities, ex-spouse relationships, military couples, the meaning of remarriage, and gender roles within contemporary families, among other topics. This volume, along with future volumes of CPFR, utilizes a wide variety of methodological and theoretical approaches, and attempts to provide a comprehensive examination of change in family structures and behaviors.
Keywords: Social Science -- Sociology -- Marriage & Family.; Family & Relationships -- Family Relationships.; Sociology: family & relationships.; Sociology.; Families.; elektronické knihy; electronic books